Antifungal effects of volatile compounds produced by Tetrapisispora sp. strain 111A-NL1 as a new biocontrol agent on the strawberry grey mold disease: Biocontrol of strawberry grey mold disease using Tetrapisispora sp. strain 111A-NL1 - Bagheri, Saman; Amini, Jahanshir; Ashengroph , Morahem; Koushesh Saba , Mahmoud (Cellular and Molecular Biology, 2022)
An antagonistic yeast strain was isolated from the strawberry fruit cv. Paros, and its antifungal properties against Botrytis cinerea causal agent of strawberry grey mold disease were evaluated under in vitro and in vivo experiments. The isolate was tentatively identified as Tetrapisispora sp. strain 111A-NL1 based on phenotypic characteristics and sequence analysis of D1/D2 domains of the 26S rRNA gene. Volatile organic compounds (VOCs) produced by the 111A-NL1 strain inhibited the mycelial growth of fungal pathogen (75.19%) and conidial germination (63.34%); however, inhibition percentage of mycelial growth of pathogen by dual culture test was less (19.49%). Also, the strain produced pectinase, siderophore, chitinase, IAA, as well as gibberellin, and could solubilize phosphate. Additionally, the disease severity of strawberry grey mold was decreased by employing living cells and volatile metabolites methods by 47.61% and 74.05%, respectively, in comparison with untreated control seven days after inoculation. Therefore, its mode of action might consist of antibiosis and VOCs production by yeast strain 111A-NL1 against B. cinerea. The VOCs released by strain 111A-NL1 were analyzed, and thirty-three chemical compounds were determined by gas chromatography-mass spectroscopy (GC-MS). Out of them, Decane (12.79%), Squalene (9.60%), Undecane (7.98%), Benzene, 1,2,3-trimethyl- (7.67%), Nonane, 2,6-dimethyl- (5.69%), Benzene, 1-ethyl-3-methyl- (5.55%), Mesitylene (4.17%), and Phenylethyl Alcohol (3.33%) were the major components. In addition, the selected strain reduced natural decay incidence and weight loss of fruit, and preserved quality parameters of strawberry fruit including firmness, soluble solids content, and titratable acidity. This research averred, for the first time, that the creation of VOCs by Tetrapisispora sp. strain 111A-NL1 could play an essential role as a biofumigant in the antifungal activity against strawberry grey mold.